Desain Pengelolaan Keuangan Bagi Bisnis Pemula: Kerangka Konseptual dalam Proses Penyajian Laporan Keuangan - Nenie Sofiyawati (Pajak dan Manajemen Keuangan, 2025)
This study addresses common problems in start-up businesses: lack of financial management and low presentation of financial statements due to limited human resources. With a conceptual qualitative research (CQR) approach, the research integrates accounting theory and business life cycle theory to design a process for presenting relevant financial statements for business actors who run individual operations. The main findings point to two things: first, the need for resources that understand finance is an inevitability that can be met through education, training, and induction observation; Second, the synthesis of accounting theory and business life cycle maps the conceptual area for the report presentation model that is tailored to the conditions of the beginner business. The proposed model covers the scope of management ranging from recording transactions on the cash mutation book, journaling to reveal the double impact of transactions, to grouping account balances on the ledger to produce relevant information. This process differs from the conventional accounting cycle in that it starts from the cashier function combined with the accounting function, thus reducing the need for separate specialists. The combination of cashier and accountant functions in one practical and relevant accounting flow for individual businesses, allows business owners to supervise their financial performance and position through simple but informative reports.